A knowledge-based social networking app for collaborative problem-solving in manufacturing. (October 2016) - Mourtzis, D.; Doukas, M.; Milas, N.
Abstract: Employees within companies act as "social machines" that process data and information, and produce valuable, yet tacit knowledge. This paper considers a smart factory framework inspired from social networking, in which employees collaborate to tackle problems related to product and production. A knowledge-based mobile app, based on the Root Cause Analysis process, formalises problem-solving instructions and expert opinions described in natural language via the Vector Space Model method. The utilised cloud infrastructure facilitates knowledge sharing and provides a business-oriented social network for employees. Both method and developed app are validated in a case study obtained from the automotive die-construction domain.